IMPROVING STUDENTS’ WRITING ACHIEVEMENT ON RECOUNT TEXT BY USING PHOTOGRAPH AT NINTH GRADE STUDENTS OF MTSN 1 MEDAN - Indah Chairani (BRIGHT VISION Journal of Language and Education, 2022)
This research was aimed to find out the impact of using Photograph in improving the students’ writing achievement on Recount Text. The subject of this research was the ninth grade students of MTsN 1 Medan in academic year of 2020/2021 which consisted of 36 students. This research was conducted by using classroom action research, which used two cycles. Each of them consists of planning, acting, observing, and reflecting. The data were obtained through quantitative and qualitative data. The quantitative data was obtained from tests including pre-test, post-test I, and post-test II. While qualitative data was obtained from observation sheet. The result of the data analysis showed that there was an improvement on the students’ reading achievement from each cycle. It was shown from the students’ mean score The precentage of students score in pre-test who got point up to 70 was 10 students and the improvement was about 27,8 %. The precentage of students score in post test 1 in cycle 1 who got point up to 70 was 25 students and the improvement was about 69,5 %. The precentage of students score in post test 2 in cycle 2 who got point up to 70 was 32 students and the improvement was about 88,9 % . Based on the finding research , saying that Photograph could improve the students’ Writing achievement in recount text.